Development of biosensors for the detection of biological warfare agents: its issues and challenges. (1st September 2013) - Kumar, Harish; Rani, Renu
This review discusses current development in biosensors for the detection of biological warfare agents (BWas). BWas include bacteria, virus and toxins that are added deliberately into air, water and food to spread terrorism and cause disease or death. The rapid and unambiguous detection and identification of BWAs with early warning signals for detecting possible biological attack is a major challenge for government agencies particularly military and health. The detection devices – biosensors – can be classified (according to their physicochemical transducers) into four types:. electrochemical, nucleic acid, optical and piezoelectric. advantages and limitations of biosensors are discussed in this review followed by an assessment of the current state of development of different types of biosensors. The research and development in biosensors for biological warfare agent detection is of great interest for the public as well as for governments.